Stabilizing Synthetic DNA for Long-term Data Storage with Earth Alkaline Salts - , A. Xavier Kohll; Antkowiak, Philipp L., Weida D. Chen; Nguyen, Bichlien, Wendelin J. Stark; Ceze, Luis; Strauss, Karin; Grass, Robert N. (Chemical Communications, 2020)
Rapid aging tests (70 °C, 50% RH) of solid state DNA dried in the presence of various salt formulations, showed the strong stabilizing effect of calcium phosphate, calcium chloride and magnesium chloride, even at high DNA loadings (>20 wt%). A DNA-based digital information storage system utilizing the stabilizing effect of MgCl2 was tested by storing a DNA file, encoding 115 kB of digital data, and the successful readout of the file by sequencing after accelerated aging.